PENGARUH PENGGUNAAN BAHAN AJAR BROSUR TERHADAP PENGUASAAN MATERI KINGDOM PLANTAE OLEH SISWA - Feri Pernando; Tri Jalmo; Berti Yolida (Universitas Lampung, 2015)
The purpose of this research was to know the influence of brochure learning material to increase materials mastery and students learning activity. The samples of this research were students of X IPA1 and X IPA2 SMAN 1 Bukit Kemuning chosen by Purposive Sampling technique. The research used pre-test-post-test non equivalent design. The quantitative data were the learning result that were analyzed by using T-Test and U-Test.The qualitative data were the observation sheet of learning activity and student responses that were analyzed descriptively. The result of students learning with N-gain average (39,94) is significantly different with class control (19,76). The increasing in the average of student learning activity of experiment class is (58,24%). Therefore, using brochure learning material can improved learning outcomes and students activity on the material of Plantae Kingdom.Penelitian ini bertujuan mengetahui pengaruh bahan ajar brosur terhadap peningkatan penguasaan materi dan aktivitas belajar siswa. Sampel penelitian ini adalah siswa kelas X IPA1 dan X IPA2 SMAN 1 Bukit Kemuning yang dipilih dengan teknik Purposive sampling. Desain penelitian menggunakan pretes-postes tak ekuivalen. Data kuantitatif berupa hasil belajar yang dianalisis menggunakan uji T dan uji U. Data kualitatif berupa aktivitas belajar dan tanggapan siswa yang dianalisis secara deskriptif. Hasil belajar siswa kelas eksperimen dengan rata-rata N-gain 39,94 berbeda signifikan dengan kelas kontrol (19,76). Peningkatan rata-rata aktivitas belajar siswa kelas eksperimen sebesar 58,24%. Sehingga, penggunaan bahan ajar brosur dapat meningkatkan hasil belajar dan aktivitas siswa pada materi pokok Kingdom Plantae.Kata kunci : aktivitas belajar, bahan ajar brosur, kingdom plantae, penguasaan materi